TRANSFORMASI GEROBAK MAKANAN TRADISIONAL PADA DESAIN KONTER MAKANAN TRADISIONAL BETAWI DI PUSAT JAJAN TEMATIK - Hendrassukma, Dila; Nediari, Amarena; Fanthi, Reno (Aksen : Journal of Design and Creative Industry, 2020)
Food cart is a medium for traditional food vendors that represents Nusantara’s culinary culture. Each food cart has the specific feature to define type of food offered. This can be recognized by its shape, color and also the sound when food cart vendors go around the street. When food cart transforms into a counter, it takes a lot of adjustment to accommodate its function from movable into fixed and the finishing technique must meet the criteria of furniture in the food court area. This paper will discuss how transformation still be able to apply Betawinese culture as inspiration to identify the food offered. The research focuses on Betawinese food cart that sell traditional Betawinese street food since it becomes the inspiration in designing food counter. The study was conducted with qualitative method by collecting primary and secondary data then processed as references in designing the counter. This is an effort to create harmony between traditional food counter and thematic food court that served Nusantara’s street food. Besides the experience in the process of serving street food can give insights to the young generation in order to preserve the sustainability of Betawinese culinary. Hopefully the result of the study can provide inspiration to the community in applying Indonesia’s culture in designing interior for commercial space.